Safety and success of exhaled breath condensate collection in asthma. Issue 4 (1st April 2003) - Baraldi, E; Ghiro, L; Piovan, V; Carraro, S; Zacchello, F; Zanconato, S
Abstract : Background: Exhaled breath condensate (EBC) is a rapidly expanding area of research to study airway inflammation through the detection of volatile and non-volatile substances in the airways. Aims: To determine the safety and feasibility of EBC procedure in a group of children with asthma of varying severity. Methods: In a cross sectional study of children aged 4–17 years, 18 healthy and 91 asthmatic children (69 in stable condition and 22 with asthma exacerbation) underwent the EBC procedure. Outcomes assessed included completion of the procedure, decrease in FEV1, change in fractional exhaled nitric oxide (FENO ), and adverse effects. No pretreatment with β2 agonists was given. All children were able to successfully complete the EBC procedure. Results: Median fall in FEV1 after the procedure was −1% (IQR −3.5, 1.8) in asthmatics and was comparable to that observed in healthy children. In only one asthmatic child did the drop in FEV1 exceed 12%. No significant changes in FENO were observed after EBC. Conclusion: This study suggests that EBC is a simple and well tolerated method for evaluating biological samples from the lower airway. The procedure was safe in children with asthma exacerbation, and the success rate was 100% in children aged 4 years and above.